A bioenergetics model to evaluate demographic consequences of disturbance in marine mammals applied to gray whales. Issue 10 (22nd October 2015) - Villegas-Amtmann, S.; Schwarz, L. K.; Sumich, J. L.; Costa, D. P.
Abstract : While sophisticated tools are used to monitor behavioral changes of large marine vertebrates, determining whether these changes are meaningful for management and conservation is challenging. The Population Consequences of Disturbance model proposed a bioenergetics model to detect biologically meaningful population responses, where disturbance costs are linked to lost energy. The model assumes that changes in behavior, caused by disturbance, compromise maternal condition, reducing energy delivery to offspring, leading to reduced reproduction, increased offspring mortality, and eventually increased adult mortality. Given its coastal habits and past whaling history, gray whales' ( Eschrichtius robustus ) life history and ecology are better known than for many other baleen whales. However, their preference for coastal habitat increases their exposure to human disturbance. We created a female gray whale bioenergetics model to determine energy requirements for a two‐year reproductive cycle and determined the consequences of lost energy under three possible disturbance scenarios. An annual energetic loss of 4% during the year in which she is pregnant, would prevent a female from successfully producing/weaning a calf. For this reason, gray whale reproduction is particularly sensitive to disturbance during pregnancy. During the year in which she is lactating, she would wean her calf at a lower mass with a 37% energetic loss. A female would lack the energy to become pregnant during a year with a 30–35% energetic loss, and female mortality would likely occur at 40–42% annual energetic loss. Our model can be used for assessing disturbance costs or other effects associated with climate change and/or anthropogenic activities and can be applied to other species with similar life histories.